Muscle Characteristics, Meat Tenderness and Nutritional Qualities Traits of Borgou, Lagunaire and Zebu Fulani Bulls Raised on Natural Pasture in Benin. (4): 2013, 5(4), 143-155 - SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; DAHOUDA, MOHAMADOU; HOUAGA, I; PICARD, B; HORNICK, J.L; MICOL, D.; KASSA, S.K.; FAROUGOU, SOUAÏBOU; MENSAH, GUY APOLLINAIRE; CLINQUART, A.; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2013)
This study was carried out to evaluate muscle characteristics, meat ten derness and nutritional qualities of Benin indigenous cattle raised on natural pasture. Thus, 10 Zebu Fulani, 10 Borgou and 5 Lagunaire were slaughtered at 5 years old and their Longissimus thoracis muscle samples were collected for analyses. Lactate dehydrogenase activity of Zebu Fulani was higher (p<0.05) than that of Lagunaire (3494 vs 2813 μmol/min/g protein) while that of Borgou was not significantly different from those of the two other breeds (p>0.05). As for isocitrate dehydrogenase, citrate synthase, cytochrome oxidase and phosphofructokinase, no significant difference was observed between the three breeds (p>0.05). By contrast, the total collagen content of Borgou (5.2 mg OH-proline/mg dry matter) was higher (p<0.01) than those of Zebu Fulani (3.1 mg OH-proline/mg dry matter) and Lagunaire (3.2 mg OH-proline/mg dry matter). The myosin heavy chain isoforms I, IIa and IIx were not different between the three breeds. The dry matter, the crude protein and the ether extract percentage were not significantly varied from one breed to another. Branched-chain Fatty Acids and saturated fatty acids contents were identical in Lagunaire and Borgou (p>0.05) while the Zebu Fulani had the highest values (p<0.05). The ratio n-6 to n-3 fatty acids obtained in the Zebu was the lower. In general, according to the fatty acids profile, Borgou and Lagunaire bulls’ meat is better than that of Zebu for heart disease.
Keywords: Beef; collagen; fatty acids; metabolic enzyme activities; mucle fibres; warner-bratzler shear force